2011
DOI: 10.1016/j.carbon.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Ball lightning plasma and plasma arc formation during the microwave heating of carbons

Abstract: Microwave heating can be used to promote heterogeneous reactions with carbon materials, mainly because of the heating mechanism involved in microwave radiation and the phenomenon known as microplasmas. This work presents photographic evidence of plasma formation when different carbon materials are subjected to microwave heating. Two different kinds of plasmas were observed: ball lightning and arc discharge plasmas. The intensity of the plasmas in the less ordered carbon was significantly higher at the beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(59 citation statements)
references
References 8 publications
2
56
0
1
Order By: Relevance
“…When CH is applied, the uniform temperature of the adsorbent is quite realistic for small beads of adsorbent with good thermal conductivity. It should also be noted that hot spots and microplasmas are observed in MH of carbons, despite MH is volumetric, in which local temperatures are much higher than the measured bulk temperature [13]. Concerning the uniform temperature of the desorber wall, it is introduced in the model due to the low thickness of the wall.…”
Section: Modelingmentioning
confidence: 98%
“…When CH is applied, the uniform temperature of the adsorbent is quite realistic for small beads of adsorbent with good thermal conductivity. It should also be noted that hot spots and microplasmas are observed in MH of carbons, despite MH is volumetric, in which local temperatures are much higher than the measured bulk temperature [13]. Concerning the uniform temperature of the desorber wall, it is introduced in the model due to the low thickness of the wall.…”
Section: Modelingmentioning
confidence: 98%
“…This is a result of field enhancement and field emission of electrons when the induced electric potential exceeds the coulomb potential. As a result of these discharges, metal tips can be melted, implying that a discharge can produce local temperatures of 1000 °C-2000 °C [25][26][27]. Our research group has studied the heating effects associated with microwave-metal discharges and found that the energy conversion ratio from electrical energy to heat can reach as high as 30% [28].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the MIP of the macroalgae industrial solid waste produces 463.9 L STP of syngas per kg of waste, which is twice the amount produced by conventional pyrolysis (232.1 L STP kg −1 ). Microwave heating initiates a process that proceeds at temperatures higher than the operating temperature due to the presence of microplasmas, consisting of hot spots that last just a fraction of a second but in that time reach temperatures considerably higher than the mean temperature [58]. This induces the thermal cracking of the volatiles into lighter gaseous molecules, such as H 2 and CO.…”
Section: Reaction Numbermentioning
confidence: 98%